1997
DOI: 10.1074/jbc.272.15.9671
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chlorophyll a and Bacteriochlorophyll a Synthases by Heterologous Expression in Escherichia coli

Abstract: Genes coding for putative chlorophyll a synthase (chlG) from Synechocystis sp. PCC 6803 and bacteriochlorophyll a synthase (bchG) from Rhodobacter capsulatus were amplified by the polymerase chain reaction and cloned into T7 RNA polymerase-based expression plasmids. In vitro enzymatic assays indicated that heterologous expression of the chlG and bchG gene products in Escherichia coli conferred chlorophyll a and bacteriochlorophyll a synthase activity, respectively. Chlorophyll a synthase utilized chlorophyllid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 21 publications
(23 reference statements)
2
88
0
1
Order By: Relevance
“…Specifically, the enzymes responsible for adding the esterifying alcohols to Chls and BChls show considerable specificity for the (B)Chlide substrate but usually have broader specificity for the esterifying alcohol (20,(51)(52)(53). In C. tepidum BchK is responsible for the addition of the farnesyl tail to BChl c, and ChlG and BchG add phytadienol and phytol to Chl a and BChl a, respectively (20).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the enzymes responsible for adding the esterifying alcohols to Chls and BChls show considerable specificity for the (B)Chlide substrate but usually have broader specificity for the esterifying alcohol (20,(51)(52)(53). In C. tepidum BchK is responsible for the addition of the farnesyl tail to BChl c, and ChlG and BchG add phytadienol and phytol to Chl a and BChl a, respectively (20).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, esterification with a long chain alcohol then yields bacteriochlorophyll a 10. It is not yet clear whether first geranylgeranyl pyrophosphate is attached followed by reduction to phytyl or whether the reduction step precedes the esterification [150,159].…”
Section: Bacteriochlorophylls a And B (Bacteriochlorins)mentioning
confidence: 99%
“…For chlorophyll a 4 the next step is simple; it involves the esterification of the C17 propionic acid group in 48 with phytyl pyrophosphate or geranylgeranyl pyrophosphate by the Chl synthase ( Figure 21) [149,150]. The enzyme is specific for chlorophyllides and cannot convert bacteriochlorophyllides.…”
Section: Chlorophylls a And Bmentioning
confidence: 99%
“…71 In vitro assays indicated that (bacterio)chlorophyllides-a were phytylated in preference to being geranylgeranylated. 72 In some purple bacterial species, geranylgeranylated bacteriochlorophyll-a 63 and tetrahydrogeranylgeranylated bacteriochlorophyll-b 73 are the final products and act as photosynthetically active pigments, while bacteriochlorophyll-g possessing a non-hydrogenated farnesyl group has been exclusively observed in heliobacteria. 49 …”
mentioning
confidence: 99%